«Una perfecta princesa». Casa y vida de la reina Isabel de Valois (1559-1568). Primera Parte - Rodriguez Salgado, M. J. (Cuadernos de Historia Moderna, 2003)
Two facts stand out in the life of Isabel de Valois: her marriage at the age of 13 to Philip II of Spain, and her death, aged 22. Her early death and the survival of some striking portraits have contributed in good measure to the aura of romantic tragedy that still envelops her. But little is known about her character or her role as queen. This study seeks to get closer to her personality and to the life she led primarily through the extant documentation about her household. It traces the personal and political forces that shaped the queen’s franco-spanish household and some of the strong pressures she was under from a young age. It demonstrates that Isabel was incapable of dealing with her vital role as head of the mass of people who made up the royal household, and examines some of the grave consequences both for individuals and for royal authority. The staggering and unsustainable debts she accumulated are also evaluated. This chapter probes deeper into how the Spanish court functioned in the sixteenth-century and explores the relative importance of personality and external limitations in the success and failure of the queen.